GREEN FINANCE IN THE GREEN ECONOMY: THEORY (Marketing Journal, 2025)
Reforms aimed at the sustainable development of the "green" economy in the world are becoming an integral part of the global trend. The level of activation of the "green" sector in the global market financial system is increasingly shifting towards green i nvestments. It is important to fully identify and practically analyze the general prospects, directions and theoretical aspects of the development of green finance. The № 10-SON OKTA BR, 2025 -YIL 512 theoretical foundations of the concept of "green" finance are investigated. The content of "green" financial instruments and institutions, their strengths and weaknesses are revealed. Green financial instruments are designed not only to obtain economic benefits from their use, but also to protect the environment, solve environmental and climate problems. The article also examines the analysis of green investments.
Keywords: green economy; green finance; green investments; low -carbon economy; environmentally responsible investments; green bonds; greening of the financial system; green technologies; carbon credit